Integrating Green Business and Value Creation for Sustainable MSMEs Performance - Sheila Najla Syahirah; Martha Fani Cahyandito; Susanti Withaningsih (International Journal of Business, Economics, and Social Development, 2026)
This study examines the integration of public policy, green business practices, and economic value creation in supporting the sustainability of micro, small, and medium enterprises (MSMEs), focusing on the case of Zunda White Tea in West Java, Indonesia. The research adopts a sustainability science perspective, emphasizing the interaction between economic, social, and environmental dimensions. Using financial analysis from 2022–2025 and applying the Economic Value Added (EVA) approach, this study evaluates whether the enterprise creates real economic value beyond accounting profits. The findings indicate that Zunda MSME demonstrates consistent financial growth, operational efficiency, and increasing profitability, supported by green business implementation such as organic inputs, eco-friendly packaging, and waste management. Furthermore, the study reveals that public policy plays a critical role in shaping sustainable agribusiness ecosystems, although its effectiveness depends on implementation consistency and alignment with MSME needs. The integration of Creating Shared Value (CSV), green business, and EVA provides a comprehensive framework for sustainable value creation. This study contributes to sustainability science by offering an integrative model that connects policy, business strategy, and financial performance in agribusiness MSMEs.